The Influence of Principal's Transformational Leadership and Work Motivation on Teacher Innovation at State Elementary Schools in Bukittinggi City - Meeka Haestetika; Sufyarma Marsudin; Anisah Anisah; Sulastri Sulastri (CV. AFDIFAL MAJU BERKAH, 2023)
This research is based on the author's observation regarding the influence of principal's transformational leadership and work motivation on teacher innovation at state elementary schools in Bukittinggi city which shows that the principal's transformational leadership is still not good, work motivation and teacher innovation are still low. The purpose of this study was to obtain data and information about (1) The influence of the principal's transformational leadership on teacher innovation at state elementary school in Bukittinggi City, (2) The influence of work motivation on teacher innovation at state elementary school in Bukittinggi City, and (3) The influence of the principal's transformational leadership and work motivation on teacher innovation at state elementary school in Bukittinggi City. This research is a correlational quantitative research with associative type. The population consisted of PNS teachers at state elementary school in Bukittinggi City, amounting to 433 people. The research sample amounted to 148 people who were taken with the Stratified Proportional Random Sampling technique, taking into account the level of education, the strata of the service period and rank/class. The research instrument used is a rating scale and a Liket Scale questionnaire which has 5 alternative answers. Before the questionnaire was used, trials were carried out to determine validity and reliability. Furthermore, the research data was analyzed with the average score (Mean) for data description, test requirements such as normality test, homogeneity test, linearity test and multicollinearity test. The results of data analysis show that: (1) principal's transformational leadership influences teacher innovation by 17.9%, (2) work motivation influences teacher innovation by 33.9%, and (3) principal's transformational leadership and work motivation together influence to teacher innovation by 36.1%. The level of achievement of teacher innovation 82.15% of the ideal score is in the high category, for principal's transformational leadership 91.12% of the ideal score is in the very good category and teacher work motivation 91.51% of the ideal score is in the very high category. The results of this research above imply that the principal's transformational leadership and work motivation are two factors that can improve teacher innovation in addition to other factors.